FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI POSYANDU DESA PRANAN KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Ditya Yankusuma Setiani; Elvara Eka Yandini (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background: Anemia in pregnancy is a decrease in hemoglobin levels occurring during pregnancy due to iron or folate deficiency. The prevalence of anemia in pregnant women in Indonesia is 37.1%. Fe toggle tablet in Indonesia in 2012 amounted to 85%. This percentage compared to the year 2011 which amounted to 83.3%. The results of preliminary study conducted in Pranan Village Midwife found as many as 47 pregnant women. At the time of interview with 10 pregnant women, 3 were anemic and can not be used for tablet consumption. Another contributing factor is the low economic status. Purpose of the study: To know the factors related to the incidence of anemia in Pregnant Women at Posyandu Pranan Village. The benefit of research is to develop and increase existing knowledge about the factors that cause the occurrence of anemia in pregnant women. The Subject: 31 pregnant women at Posyandu Pranan Village The Method: Used descriptive analytic method with cross sectional approach. This study to determine the factors associated with the incidence of anemia in pregnant women. Sampling in total sampling. The data obtained were analyzed by Chi Square test with p = 0.05. Result: Showed that there was correlation between pregnancy distance with the incidence of anemia (p = 0,028) and there was correlation between smoking with the incidence of anemia in pregnant mother in Pranan Village (p = 0,026 ). However, there was no correlation between economic status and the occurrence of anemia (p = 0.442) and there was no correlation between routine consumption of iron tablets and the incidence of anemia in pregnant women in Pranan Village (p = 0.863). Conclusion: There is a relationship between pregnancy distance and smoking with the incidence of anemia and there is no relationship between economic status and iron consumption routine with the incidence of anemia. Keywords: stress level, menstrual cycles